Migration, Trade, and Foreign Direct Investment in Mexico - Aroca Gonzalez, Patricio; Maloney, William F. (World Bank, Washington, DC, 2012)
Part of the rationale for the North American Free Trade Agreement (NAFTA) was that it would increase trade and foreign direct investment (FDI) flows, creating jobs and reducing migration to the United States. Since poor data on illegal flows to the United States make direct measurement difficult, Aroca and Maloney instead evaluate the mechanism behind these predictions using data on migration within Mexico where the census data permit careful analysis. They offer the first specifications for migration within Mexico, incorporating measures of cost of living, amenities, and networks. Contrary to much of the literature, labor market variables enter very significantly and as predicted once the authors control for possible credit constraint effects. Greater exposure to FDI and trade deters out-migration with the effects working partly through the labor market. Finally, the authors generate some tentative inferences about the impact on increased FDI on Mexico-U.S. migration. On average, a doubling of FDI inflows leads to a 1.5-2 percent fall in migration.